Open vs. Proprietary Source Software in Croatia - Lazić, Nikolaj (Array, 2009)
This paper shows differences between open source software and proprietary source software from the Croatian user perspective. These confronting approaches have their own positive and negative aspects which are viewed through present 2009 financial crisis and the need for lifelong learning projects promoted by the Croatian Ministry of Science, Education and Sports. User survey was conducted at the Faculty of Humanities and Social Sciences, University of Zagreb.